Effect of the slip conditions with rotation, wall properties and heat transfer on peristaltic transport MHD - Nahi, Hatem; Hatem, Mustafa (Iraqi Journal of Science, 2025)
In this study, we look into how the peristaltic flow MHD is affected by rotation, heat transfer, elasticity wall characteristics, and slip conditions. For simplification, the governing equations, infinite wavelength and small Reynolds numbers have been used to study the Newtonian fluid in a porous canal. Heat transport, elasticity, rotation, and slip conditions are taken into account. The Brinkman number, Hartman number, and other parameters are evaluated to observe their effects on the stream function, temperature, velocity, and coefficient of heat transfer. The results indicate that when these parameters are varied, more trapped boluses develop. Figures and graphs discuss and illustrate the impact of various values on these factors. The MATHEMATICA software has been used to compute numerical results.